Perbedaan Tekanan Darah Sistolik dan Diastolik Pada Kelompok Lanjut Usia Dengan Insomnia - Djung Lilya Wati; Meilani Kumala; Zita Atzmardina; Fernando Nathaniel; Dean Ascha Wijaya (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Insomnia is the most common sleep disorder experienced by the elderly, which has a significant negative effect on morbidity and mortality in the elderly group. A study from the Penn State Adult Cohort found that people who are sleep deprived with objectively short sleep duration have a higher risk of developing hypertension. This cross-sectional study aims to determine differences in systolic and diastolic blood pressure in the elderly group (³60 years) with insomnia which were selected consecutively at the Tarumanagara University COVID-19 Vaccine Center for the period March – April 2021. The Insomnia Severity Index (ISI) questionnaire was used to evaluate the severity of insomnia. Blood pressure is measured with a digital tensimeter according to standard procedures. Statistical analysis using the Mann Whitney test. Of the 119 respondents, the average age was 69.84 years and 58% of the respondents were women. The mean systolic blood pressure was 150.18 and the average diastolic blood pressure was 83.23. From all respondents, it was found that 17.6% of respondents experienced insomnia. The results of the Mann Whitney statistical test explained that there was no difference in the mean systolic and diastolic blood pressure in the group with insomnia and without insomnia (p-value > 0.05). Further clinical studies revealed that the group of elderly who had insomnia tended to have higher blood pressure than the group of elderly who did not experience insomnia (SBP: 160 vs 151; DBP: 85 vs 84). Dealing with insomnia can be an effort to lower blood pressure.